AN ANALYSIS OF FIGURATIVE LANGUAGE USED IN THE LYRICS OF A THOUSAND LOVE SONGS - Masayu Soraya; Trisnendri Syahrizal (PROJECT (Professional Journal of English Education), 2023)
Literature is a term that describes written text characterized by careful use of language, including features such as creative metaphors, beautiful phrase, elegant syntax, rhymes, and aesthetic alliterations. This research analyzed the figurative language used in the lyrics of A Thousand Love Songs by The Light The Heat. The purpose of this research study is to know the types of figurative languages used. This research study using descriptive qualitative method and library research to obtain the data. Researcher searced the lyrics on internet. From the study, some figurative languages were found such as Hyperbole, Metaphor, Litotes, Personification, Symbol, and Synecdoche. Hyperbole is the most used figurative language. In this article, there are also explanations of implicit meaning of each figurative language being used based on the context.